The Determinants of Food Insecurity among Food Bank Clients in the United States. Issue 3 (7th September 2017) - Gundersen, Craig; Engelhard, Emily; Hake, Monica
Abstract : The majority of poor households in the United States are food secure which is both surprising and not well‐understood. We increase our understanding by looking at a particularly vulnerable group—people visiting food pantries—through the use of the Hunger in America (HIA) 2014 data set. Along with providing information on households often overlooked in other data sets, HIA has a wide array of questions. We find, in comparison to food secure households, that food insecure households are more likely to have challenges paying their bills and are more likely to use coping mechanisms. These effects are large, especially when compared to the standard set of explanatory variables. We also find that the impact of the standard set of covariates change dramatically when we include variables that are often unobserved, suggesting that there may be biases in some of the central findings on the determinants of the food insecurity.